Sex difference in the impact of smoking on Clinical outcomes following LVAD implantation. (25th November 2020) - Imamura, T; Combs, P; Siddiqi, U; Mirzai, S; Stonebraker, C; Bullard, H; Simone, P; Jeevanandam, V
Abstract: Background: Smoking would have a negative impact on clinical outcomes following left ventricular assist device (LVAD) implantation. However, its impact on male and female cohorts separately remains uninvestigated. Purpose: We aimed to investigate the association between smoking and post-LVAD outcomes among male and female cohorts separately. Methods: Data of consecutive patients who received LVAD implantation at our institute between Jan 2013 and Sep 2018 were retrospectively reviewed. Clinical outcomes were compared between the never smokers and the current smokers among male and female cohorts separately. Those with former smoking were excluded. Results: Of all, 85 male patients (median 56 years old) and 45 female patients (median 56 years old) were included. Among the male cohort, total readmission rate was higher in the current smokers than never smokers (incidence rate ratio 1.51, p=0.09). Rates of gastrointestinal bleeding, stroke, and hemolysis trended to be higher in current smokers (Figure 1A). Among the female cohort, these rates were not different irrespective of the smoking status (Figure 1B). Survival was not different irrespective of smoking status among both male and female cohorts. Conclusion: The impact of smoking on post-LVAD outcomes seems to be different between males and females. Different therapeutic strategy might be required for the LVAD candidates with active smoking between male and female cohort. Funding Acknowledgement: Type of funding source: None